The pH-responsive transcription factor PacC regulates mycelial growth, fruiting body development, and ganoderic acid biosynthesis in Ganoderma lucidum. (1st November 2016) - Wu, Feng-Li; Zhang, Guang; Ren, Ang; Dang, Zhi-Hao; Shi, Liang; Jiang, Ai-Liang; Zhao, Ming-Wen
Abstract: Ganoderma lucidum is a medicinal macrofungus that is widely used in traditional Chinese medicine. Nonetheless, the scarcity of basic biological studies of this organism has hindered the further development of its commercial value. The pH-responsive transcription factor PacC/Rim101 governs the adaptation to environmental pH, the development and the secondary metabolism of many fungi. In this study, a homologue of PacC/Rim101 that encodes GlPacC was identified in the higher basidiomycete G. lucidum . GlPacC is composed of 807 amino acids and contains three typical C2H2 zinc-finger domains, two potential PEST domains, a putative PKA phosphorylation site, and a putative nuclear localization signal (NLS). GlPacC was transcribed at a high level when the fungus was under neutral and alkaline conditions, and silencing of GlPacC impaired the fungal response to ambient pH. The distance between the hyphal branches (of vegetative hyphae and aerial hyphae) was significantly increased in the GlPacC -silenced strains. The GlPacC -silenced strains grew abnormally or became sickly on solid culture medium and were unable to form primordia and fruiting bodies. The ganoderic acid content, levels of the sqs and ls transcripts, and contents of the metabolic intermediates squalene and lanosterol were all up-regulated in the GlPacC -silenced strains. Our results indicate that GlPacC is functional and plays complex roles in mycelial growth, fruiting body development and ganoderic acid biosynthesis in G. lucidum .